ANALISIS POTENSI DAN MASALAH PARIWISATA DI KELURAHAN KANDRI - Tjahjono, Heri (Faculty of Social Science, Universitas Negeri Semarang, 2010)
Kelurahan Kandri is one of the villages in Semarang which will be planned as a Ã¢â‚¬Å“Tourism VillageÃ¢â‚¬Â.In the near Future in addition to the plan, a reservoir Waduk Jatibarang, will be built in part of its area. Inconsequence to this condition, a slight impact on new live patterns may emerge resulting in behaviouralmodifi cation/changes, which may either encourage or discourage the tourism itself. This Research isconducted by purposive sampling, and the variables observed cover; (1) the tourism potential in KelurahanKandri; (2) the preparation of Kandri Society to be tourism village; (3)the encouraging and discouragingelements for the village to be made a tourism village; (4) the effort to develop the potential of tourism inKelurahan Kandri. The result show that the tourism potential which can be developed covers; (1) Naturaltourism such as Kreo cave; waterfall (2)cultural tourism, such as the Talun Kacang Rebana Group, Ketoprakand Dangdut music group; also cultural tourism of Ã¢â‚¬Å“ Waduk JatibarangÃ¢â‚¬Â, which is under constructionof the reservoir, among ather are; (a) preparing a professionexchange by giving additional skill besidefarming; (b) preparing human resources improvement; (c) Suggesting the local people such are buildinghouses to add the number of toilet or rest room so that the house can also be made as a Ã¢â‚¬Å“home stayÃ¢â‚¬Â forthe tourists to rent. The encouraging elements for developing the tourism cover; The scenic beauty of itsnature, the socio cultural of the community/ local people or their hospitality in welcoming the tourist,and the effortless of accessibility.Key words: Potential tourism, Kandri